The concise measurement of clinical communication skills: Validation of a short scale - Maaß, Ulrike; Kühne, Franziska; Heinze, Peter Eric; Ay-Bryson, Destina Sevde; Weck, Florian (Frontiers in Psychiatry, 2022)
Objective: There is a lack of brief rating scales for the reliable assessment of psychotherapeutic skills, which do not require intensive rater training and/or a high level of expertise. Thus, the objective is to validate a 14-item version of the Clinical Communication Skills Scale (CCSS-S). Methods: Using a sample of N = 690 video-based ratings of role-plays with simulated patients, we calculated a confirmatory factor analysis and an exploratory structural equation modeling (ESEM), assessed convergent validities, determined inter-rater reliabilities and compared these with those who were either psychology students, advanced psychotherapy trainees, or experts. Results: Correlations with other competence rating scales were high (rs > .86 to .89). The intraclass correlations ranged between moderate and good (ICC(2,2) = .65 to .80), with student raters yielding the lowest scores. The one-factor model only marginally replicated the data, but the internal consistencies were excellent (𝛂 = .91 to 95). The ESEM yielded a two-factor solution (Collaboration and Structuring and Exploration Skills). Conclusion: The CCSS-S is a brief and valid rating scale that reliably assesses basic communication skills, which is particularly useful for psychotherapy training using standardized role-plays. To ensure good inter-rater reliabilities, it is still advisable to employ raters with at least some clinical experience. Future studies should further investigate the one- or two-factor structure of the instrument.